Fragmented Identities and Feminist Schizoanalysis: Reimagining the Self in Contemporary American Fiction - Singh, Pushpraj; Rana, Ekta (Journal of Studies in the English Language, 2025)
Fragmented identity is not merely a theme in the works of Toni Morrison, Roxane Gay, and Don DeLillo—it is embedded in the very structure of their narratives. This paper examines how fragmentation functions as both theme and form in selected contemporary American fiction. Bringing together Deleuze and Guattari’s schizoanalysis with feminist psychoanalytic thought from Kristeva and Irigaray, this study engages with the ways in which literary form becomes a site for negotiating trauma, memory, and dislocation. Using a close textual analysis of Beloved, An Untamed State, Difficult Women, and White Noise, the study explores how these narratives challenge the notion of a coherent self. Nonlinear timelines, disjointed syntax, and shifting voices echo the fragmented psyche, where trauma distorts time, language falters, and identity refuses containment. Morrison’s haunted maternal bodies, Gay’s fractured yet resisting women, and DeLillo’s media—ghosted men reveal not a loss of self, but its reassembly through dissonance. The findings suggest that these texts do not attempt to resolve fragmentation, but rather dwell within it—offering a literary and theoretical map of the disassembled self. Rather than seeking closure or resolution, these texts remain with the broken—where meaning is unstable, but no less urgent. This study contributes to feminist and post—structuralist literary scholarship by demonstrating how schizo—feminist readings illuminate the interplay between narrative form and identity construction in the postmodern era.